2019
DOI: 10.1002/anie.201910558
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Oligomeric Ligands Prepared via Radical Polymerization that Recognize and Neutralize a Target Peptide

Abstract: Abiotic ligands that bind to specific biomolecules have attracted attention as substitutes for biomolecular ligands, such as antibodies and aptamers. Radical polymerization enables the production of robust polymeric ligands from inexpensive functional monomers. However, little has been reported about the production of monodispersed polymeric ligands. Herein, we present homogeneous ligands prepared via radical polymerization that recognize epitope sequences on a target peptide and neutralize the toxicity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 44 publications
0
35
0
Order By: Relevance
“…The target peptides could be immobilized on beads and loaded into a chromatography column with the synthetized oligomers separated according to their interactions with the respective peptides (refer to Section 3.3.2). 108 …”
Section: Synthetic Approaches To Defined Oligomersmentioning
confidence: 99%
See 3 more Smart Citations
“…The target peptides could be immobilized on beads and loaded into a chromatography column with the synthetized oligomers separated according to their interactions with the respective peptides (refer to Section 3.3.2). 108 …”
Section: Synthetic Approaches To Defined Oligomersmentioning
confidence: 99%
“…The target peptides could be immobilized on beads and loaded into a chromatography column with the synthetized oligomers separated according to their interactions with the respective peptides (refer to Section 3.3.2). 108 Hybrid methodologies that combine stepwise strategies with purification of oligomer mixtures have recently been developed and offer gains when compared to traditional approaches, especially to higher molecular weight systems. This is exemplified by the synthesis of welldefined conjugated materials by Otsubo and coworkers.…”
Section: Defined Oligomers Via Purificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Sequence specificity was observed in the case of homogeneous di-block oligomers of A and T. 20 A di-block hexamer consisting of 4 units of A and 2 units of T recognize negatively charged KRKR sequence on melittin, though, the hexamer consisting of 2 units of A and 4 units of T recognized hydrophobic amino acids including tryptophan next to the KRKR sequence. 20 These results demonstrated that the synthetic oligomer ligands, which effectively interact with the target peptide via multi-modal interactions, can be prepared by controlling the block sequence of the multi-functional oligomers. Screening of mono-, di-, and tri-block oligomer ligands revealed that not only the localization and combination of functional groups but also the sequence of the functional block and end groups are of importance to design high affinity ligands that binds and neutralize activity of target biomacromolecules.…”
mentioning
confidence: 99%